Detailed Study on Total Information Score, Multivariate Analysis and Usefulness of Agricultural Knowledge and Information of Irrigation Farmers in North Western Nigeria - Lawal Iro Sani; Umar Maiwada (New Ideas Concerning Science and Technology Vol. 4, 2021)
A principal component which is concern with explaining the variance-covariance structure of a set of variables through a few linear combinations of these variables is usually referred to as multivariate. Any system producing or containing information intended for transmission is an information source. This study examines the use of multivariate statistical analysis and total information score for information sources of irrigation farming in North western Nigeria. A questionnaire survey of 368 household was used to explore the impact of information sources in accessing agricultural information by irrigation farmers. Three States were studied using qualitative and quantitative research approach. The results of the study revealed that irrigation farmers in the study area opted to use information emanating from public and private sources. The results further reveal that there is a strong positive linear relationship between agricultural information needs of irrigation farmers and the sources of that information. The study therefore, suggested that in order to fill the information gaps of the irrigation farmers, more sources should be explored and be made available to the irrigation farmers. The type and level of training depend on the readiness of the agricultural information centres (ministries), user-researcher, extension workers and rural irrigation farmers and policy makers. This is because the lack of articulated agricultural information user training down to the grass-root level has often impeded the dissemination of agricultural information to the farmers.